Risk Factors of Uncontrolled Hyperglycemia in Children and Adolescents with Type 1 Diabetes Mellitus - Shukur Abdulkareem Mahmood; Majid A. Maatook; Dhaigham E. Aatwan (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: In Iraqi children with type 1 diabetes mellitus, glycemic control levels and risk factors for uncontrolled hyperglycemia are unknown. The aim of the study to assess the factors that increase the risk of uncontrolled hyperglycemia in children and adolescents with type 1 diabetes mellitus, and identify levels of glycemic control in children and adolescents with type 1 diabetes mellitus.Methods: A cross-sectional study was carried out from September 21 2020 until the end of May 2021 to identify levels of glycemic control and assess the risk factors of uncontrolled hyperglycemia in children and adolescents with type 1 diabetes mellitus, for the study sample which was 209 type 1 diabetics, selected randomly from the visitors of a Faiha Specialized Diabetes, Endocrine, and Metabolism Center (FDEMC). The American Diabetes Association assigned target HbA1c levels to patients based on their age groups. Comparison has been made of well-controlled patients and uncontrolled hyperglycemia patients. To assess each risk factor’s role in uncontrolled type 1 diabetes hyperglycemia, the Odds Ratios were calculated.Results: Only 17.2% of children and adolescents with type 1 diabetes mellitus were well-controlled diabetes. Better glycemic control was related to age < 6 years, BMI, and duration of type 1 diabetes <5 years. Glycemic control was not affected by gender, residence, socio-economic status. Conclusion: Type 1 diabetes mellitus glycemic control among children and adolescents in Al-Basra/southern Iraq varies widely, risking microvascular complications. In well-control type 1 diabetes mellitus patients, females were higher than males and in the age group (1-6) years, higher than the other age groups. While in uncontrolled patients with type 1 diabetes, about (57.2%) had an episode of diabetic ketoacidosis (DKA). The major risk factors for uncontrolled hyperglycemia are excessive sweet intake, fast food, and irregular meals